Improved draught power use for increased food and feed production on Ethiopian highland vertisols - Asamenew, G.; Jutzi, S.C.; Tedla, A.; McIntire, John M.; Ikavalko, E. (Institute of Agricultural Research, 1989)
Presents and discusses the effects of animal power use for improved soil surface drainage on food and feed production on the vertisols of the Ethiopian highlands. Examines the on-farm technology validation programme at ILCA; describes crop/livestock interactions in these vertisol areas; highlights the seasonal pattern of draft oxen use; and assesses the economic impact of animal power use for surface drainage.